Penentuan Penerima Bantuan Siswa Miskin Menerapkan Metode Multi Objective Optimization on The Basis of Ratio Analysis (MOORA) - Dwika Assrani; Nurul Huda; Rudi Sidabutar; Imam Saputra; Oris Krianto Sulaiman (JURIKOM (Jurnal Riset Komputer), 2018)
The BSM Program is a National Program aimed at eliminating the barriers of poor students participating to school by helping poor students obtain proper access to education services, preventing dropping out, attracting poor students to return to school, helping students meet needs in learning activities, supporting compulsory education programs 9 Years (even up to middle level), as well as help smooth school programs. To obtain the Poor Student Assistance (BSM) fund, the government sets out some criteria for who are the students who can be eligible and entitled to receive Poor Student Assistance (BSM). The criteria will be later that will assist the school or educational institution in determining which students can be eligible to receive Poor Student Assistance Fund. Therefore, an educational institution must have a Decision Support Support System of Poor Student Fund (BSM) using Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method, with a decision support system of Poor Student Assistance (BSM) is expected to be successful, on target, and accepted by the rightful person. Thus the decision maker can compare the performance between the old system with the BSM funding decision support system with the method of Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) without having to ask back the data of students who will be given Poor Student Assistance funds.